DILEMA YURIDIS TENTANG KOMPETENSI LEMBAGA KEUANGAN SYARI'AH DALAM PENGELOLAAN DAN PENGEMBANGAN WAKAF UANG - Siddiq, Achmad (Khatulistiwa, 2013)
One form of endowments that introduced new legislation on charitable endowments Indonesia is money. Management and development of charitable money entrusted by legislation to the Financial institutions considering shariah professionalism owned by the agencies in managing the Islamic finance in addition to meet the required characteristics of endowments guarantee the integrity of the property anyway. But this may still be at the level seen in idealitas whenever practical level where the purity Islamic financial institutions in implementing the principles of sharia realatif not total, because it will see is the management and development of charitable money through investment in Money Market Invesment schemes Mudaraba through inter-bank or Wadiah Bank Indonesia Certificates. This is done by the Islamic Financial Institutions in order to minimize investment risk to meet the characteristics of endow-ments, but the main goal in “mensejahterahkan” people through direct investment or development of real sector of high risk postscript far from expectations.